Testicular growth and its relationship with linear body measurements in Borana-Friesian crossbred bull calves at different ages - Gojam, Y.; Tegegne, Azage; Gebre-Wold, A.; Alemayehu, M.; Yilma, Z. (Ethiopian Society of Animal Production, 2002)
Measurements on testis and linear body size, scrotal circumference (SC), testis diameter (TD) hearth girth (HG), height at wither (HTW) and body length (BDL) at the age of 1, 3, 6, 9, 12, 15, 18 and 21 months was taken. Thirteen Borana Friesian (BoXF) crossbred bull calves born at Holetta Agricultural Research Centre (HARC) during the year 1998/99 calving season were used. The objective of the work was to determine the testis and body size of the bullcalves and their relationship at different ages to consider as criterion for early selection of breeding bulls. Statistical analysis indicated that significantly different (P<0.001) rate of increase in testis and body size of measured variables between age groups. However the magnitude of increase in size of TD, SC, HG, HTW, and BDL was not significant (P<0.05) in the age group between 18 & 21 months. Body weight (Wt) have influenced in increase of SC (P<0.001) and TD, HTW and BDL (P<0.05). HG, BDL and HTW were positive and significantly (P<0.001) correlated to TD and SC respectively, r=0.94, 0.92 and 0.68 respectively. It appears evident from the results of this study, that sexual maturity could be attained in Box F from closer to 15 months of age, since the increasing rate of testis size was lower and steady after this age. Even if the determination of sexual maturity in male needs detail examination and is complex, at field level the steady change in testis and body size may indicate the inclination of the animal to physiological maturity. The result also suggests that testis size could be described in terms of body size. Further study in this line may deal with determination of quality and quantity of semen at different ages of bull calves for indigenous and different genotypes, since the information available is quiet insufcient.